ANALISIS PENGARUH JUMLAH TABUNGAN DAN DEPOSITO TERHADAP JUMLAH KREDIT PADA PD. BPR BKK BANJARHARJO KABUPATEN BREBES - Yuliawan, Hendry (PERMANA, 2014)
This study aims to determine how the effect of savings and deposits to total loans disbursed on the PD. BPR BKK Banjarharjo Brebes and to determine which variable greatly affect the amount of loans extended to the PD. BPR BKK Banjarharjo Brebes. Savings have a positive and significant effect on the amount of loans extended to the PD. BPR BKK Banjarharjo Brebes. This can be demonstrated by using test t count test using a 95 percent confidence level (Î± / 2 = 0.05 / 2 = 0.025) and the degree of freedom Nk (5-2) obtained t table of 3.182 and the results of calculations in SPSS show X1 = 6.399 which means that t count > t table. It shows that Ho is rejected or variable savings significantly affect the credit. While the X2 obtained 0.278 which means that tcount < t table. It shows that Ho accepted or deposits not significantly affect the credit.